ESAT6-induced IFNgamma and CXCL9 can differentiate severity of tuberculosis. - Zahra Hasan; Bushra Jamil; Mussarat Ashraf; Muniba Islam; Muhammad S Yusuf; Javaid A Khan; Rabia Hussain (PLoS ONE)
Background Protective responses against Mycobacterium tuberculosis are dependent on appropriate T cell and macrophage activation. Mycobacterial antigen six kDa early secreted antigenic target (ESAT6) and culture filtrate protein 10 (CFP10) can detect M. tuberculosis specific IFNgamma responses. However, most studies have been performed in non-endemic regions and to study pulmonary tuberculosis (PTB). We have studied ESAT6 and CFP10 induced cytokine and chemokines responses in PTB and extrapulmonary (EPul) TB. Methodology IFNgamma, IL10, CXCL9 and CCL2 responses were determined using an ex vivo whole blood assay system in PTB (n = 30) and EPulTB patients with limited (LNTB, n = 24) or severe (SevTB, n = 22) disease, and in healthy endemic controls (ECs). Responses to bacterial LPS were also determined. Principal findings ESAT6- and CFP10-induced IFNgamma was comparable between ECs and TB patients. Both ESAT6- and CFP10-induced IFNgamma secretion was greater in LNTB than PTB. ESAT6-induced CXCL9 was greater in EPulTB as compared with PTB, with an increase in SevTB as compared with LNTB. CFP10-induced CCL2 was higher in PTB than LNTB patients. LPS-stimulated CXCL9 was greatest in SevTB and LPS-induced CCL2 was increased in PTB as compared with LNTB patients. A positive correlation between ESAT6-induced IFNgamma and CXCL9 was present in all TB patients, but IFNgamma and CCL2 was only correlated in LNTB. ESAT-induced CCL2 and CXCL9 were significantly associated in LNTB while correlation in response to LPS was only present in SevTB. Conclusions ESAT6 induced IFNgamma and CXCL9 can differentiate between limited and severe TB infections.